Microsatellite instability evaluation: which test to use for endometrial cancer?. Issue 1 (26th July 2021) - Rafaniello-Raviele, Paola; Betella, Ilaria; Rappa, Alessandra; Vacirca, Davide; Tolva, Gianluca; Guerrieri-Gonzaga, Aliana; Bertario, Lucio; Barberis, Massimo; Bonanni, Bernardo; Marabelli, Monica
Abstract : Aims: Analysis of microsatellite instability (MSI) is strongly recommended in endometrial cancer (EC) and colorectal cancer to screen for Lynch syndrome, to predict prognosis and to determine optimal treatment and follow-up. In a large monoinstitutional series of ECs, we evaluated the reliability and accuracy of Idylla assay, a rapid, fully automated system to detect MSI, and we compared its performance with two routine reference methods. Methods: We evaluated MSI status in 174 formalin-fixed, paraffin-embedded EC tissue samples using immunohistochemistry (IHC) for mismatch repair (MMR) proteins and Idylla assay. Samples with discordant or equivocal results were analysed with a third technique, the Promega MSI kit. Results: Idylla MSI assay and IHC were highly concordant (overall agreement: 154/170=90.59%, 95% CI 85.26% to 94.12%). However, in four samples, MMR-IHC staining was equivocal; moreover, 16 cases showed discordant results, that is, MMR deficient using IHC and microsatellite stable using Idylla. These 20 samples were reanalysed using the MSI-Promega kit, which showed the same results of Idylla assay in 18/20 cases (overall agreement: 90%, 95% CI 69.90% to 97.21%). Conclusions: Our results suggest that IHC is an efficient method to determine MMR status in ECs. However, the Idylla MSI assay is a rapid and reliable tool to define MSI status, and it could represent a valuable alternative to conventional MSI-PCR methods.